Socialization, legitimation and the transfer of biomedical knowledge to low- and middle-income countries: analyzing the case of emergency medicine in India - Veena Sriram; Asha George; Rama Baru; Sara Bennett (BMC, 2018)
Abstract Background Medical specialization is a key feature of biomedicine, and is a growing, but weakly understood aspect of health systems in many low- and middle-income countries (LMICs), including India. Emergency medicine is an example of a medical specialty that has been promoted in India by several high-income country stakeholders, including the Indian diaspora, through transnational and institutional partnerships. Despite the rapid evolution of emergency medicine in comparison to other specialties, this specialty has seen fragmentation in the stakeholder network and divergent training and policy objectives. Few empirical studies have examined the influence of stakeholders from high-income countries broadly, or of diasporas specifically, in transferring knowledge of medical specialization to LMICs. Using the concepts of socialization and legitimation, our goal is to examine the transfer of medical knowledge from high-income countries to LMICs through domestic, diasporic and foreign stakeholders, and the perceived impact of this knowledge on shaping health priorities in India. Methods This analysis was conducted as part of a broader study on the development of emergency medicine in India. We designed a qualitative case study focused on the early 1990s until 2015, analyzing data from in-depth interviewing (n = 87), document review (n = 248), and non-participant observation of conferences and meetings (n = 6). Results From the early 1990s, domestic stakeholders with exposure to emergency medicine in high-income countries began to establish Emergency Departments and initiate specialist training in the field. Their efforts were amplified by the active legitimation of emergency medicine by diasporic and foreign stakeholders, who formed transnational partnerships with domestic stakeholders and organized conferences, training programs and other activities to promote the field in India. However, despite a broad commitment to expanding specialist training, the network of domestic, diasporic and foreign stakeholders was highly fragmented, resulting in myriad unstandardized postgraduate training programs and duplicative policy agendas. Further, the focus in this time period was largely on training specialists, resulting in more emphasis on a medicalized, tertiary-level form of care. Conclusions This analysis reveals the complexities of the roles and dynamics of domestic, diasporic and foreign stakeholders in the evolution of emergency medicine in India. More research and critical analyses are required to explore the transfer of medical knowledge, such as other medical specialties, models of clinical care, and medical technologies, from high-income countries to India.